EffectOf Panax Ginseng Extract For The Increased Number Of Fibroblasts Cells After Tooth Extraction - Ferdian Rizky Hutomo; Nur Permatasari; Kartika Andari Wulan (Universitas Muhammadiyah Yogyakarta, 2012)
The process of tooth extraction can lead to injury. One of the factors that influence the process of wound healing after tooth extraction is the number of fibroblast cells. The content of saponins can increase the number of fibroblasts cells after tooth extraction. Asian ginseng plants known to contain saponins (ginsenoside). The purpose of this study was to determine the effect of Asian ginseng extract (Panax ginseng extract) for the increased number of fibroblasts cells after tooth extraction. The research method used is in vivo experimental design with the design methods Randomized Post Test Only Control Group Design. In this study used twentty male rattus novergicus and divided into four group, consisting of control group (K1) were not given Asian ginseng extract, treatment groups number one (K2) were given 25mg/Rattus novergicus/day doses of Asian ginseng, treatment groups number two (K3) were given 50mg/ Rattus novergicus/day doses of Asian ginseng, and treatment groups number three (K4) were given 75mg/Rattus novergicus/day doses of Asian ginseng. Histopathologic preparations used for counting the number of fibroblasts cells. The results of statistical tests indicate there are differences in the number of fibroblast cells in Rattus novergicus between the four different groups (ANOVA, p 0.05) and there is a very strong correlation between increasing doses of ginseng extract with a number of fibroblast cells in Rattus novergicus tooth socket (Pearson, R = 0.915 p 0.05). The conclusion of this study is Asian ginseng extract can increase the number of fibroblasts in the tooth socket after tooth extraction, it is recommended that research about the amount of saponin in Asian Ginseng extract